Anti-inflammatory activity of essential oils from Tunisian aromatic and medicinal plants and their major constituents in THP-1 macrophages. (May 2023) - Pereira, Renato B.; Rahali, Fatma Zohra; Nehme, Ralph; Falleh, Hanen; Jemaa, Mariem Ben; Sellami, Ibtissem Hamrouni; Ksouri, Riadh; Bouhallab, Said; Ceciliani, Fabrizio; Abdennebi-Najar, Latifa; Pereira, David M.
Graphical abstract: Highlights: EOs obtained from Mediterranean aromatic herbs are anti-inflammatory agents. Coriander, geranium and wormwood EOs inhibit NF-κB and caspase-1 activation. Linalool and β-citronellol explain the anti-inflammatory properties of the EOs. α-Thujone together with camphor mimic the anti-inflammatory activity of wormwood EO. β-citronellol inhibits caspase-1 activation in LPS-stimulated THP-1 macrophages. Abstract: In this study, the capacity of eight essential oils (EOs), sage ( Salvia officinalis ), coriander ( Coriandrum sativum ), rosemary ( Rosmarinus officinalis ), black cumin ( Nigella sativa ), prickly juniper ( Juniperus oxycedrus ), geranium ( Pelargonium graveolens ), oregano ( Origanum vulgare ) and wormwood ( Artemisia herba-alba ), on the inhibition of NF-κB activation was screened at concentrations up to 0.25 µL/mL using THP-1 human macrophages bearing a NF-κB reporter. This screening selected coriander, geranium, and wormwood EOs as the most active, which later evidenced the ability to decrease over 50 % IL-6, IL-1β, TNF-α and COX-2 mRNA expression in LPS-stimulated THP-1 macrophages. The chemical composition of selected EOs was performed by gas chromatography–mass spectrometry (GC–MS). The two major constituents (>50 % of each EO) were tested at the same concentrations presented in each EO. It was demonstrated that the major compound or the binary mixtures of the two major compounds could explain the anti-inflammatory effects reported for the crude EOs. Additionally, the selected EOs also inhibit>50 % caspase-1 activity. However, this effect could not be attributed to the major components (except for β-citronellol/geranium oil, 40 %/65 % caspase-1 inhibition), suggesting, in addition to potential synergistic effects, the presence of minor compounds with caspase-1 inhibitory activity. These results demonstrated the potential use of the EOs obtained from Tunisian flora as valuable sources of anti-inflammatory agents providing beneficial health effects by reducing the levels of inflammatory mediators involved in the genesis of several diseases.